PENAFSIRAN KONTEKSTUAL AL-QUR’AN: TELAAH ATAS PEMIKIRAN ABDULLAH SAEED - Asroni, Ahmad (Living Islam: Journal of Islamic Discourses, 2021)
This article discusses Abdullah Saeed's thought on contextual exegesis of the Quran. The background of Abdullah Saeed's thought on the importance of conducting contextual exegesis was based on the solid domination of literal (textual) commentary of the Quran, particularly regarding ethics-legal verses. Based on Saeed's point of view, ethic-legal verses commentary must account for social changes to support the close relationship between Quran and the current Muslims. Several intellectual figures influenced Abdullah Saeed's thoughts related to contextual exegeses, such as Fazlur Rahman, Ghulam Ahmad Parvez, Nasr Hamid Abu Zayd, Mohammed Arkoun, Farid Esack, and Khaled Abou El Fadl. The theoretical foundations of the Quran contextual exegesis proposed by Abdullah Saeed can be traced back through his notion on revelation concept, the flexibility of meaning, and text meaning as a commentary.